Prevalence and characteristics of intended adolescent pregnancy: an analysis of the Canadian maternity experiences survey - Sekharan, Vineeth S. (Reprod Health, 2015)
BACKGROUND: There is limited research focusing on adolescent women who intended to become pregnant, as majority of research examines unintended adolescent pregnancies. The objective was to examine the prevalence and characteristics of Canadian adolescent women who intended to become pregnant. METHODS: The analysis was based on the national 2006 Maternity Experiences Survey consisting of women who had a singleton live birth. The sample was restricted to adolescent women between 15 to 19 years of age. The main outcome of this study was the adolescent woman’s pregnancy intention. A variety of sociodemographic, maternal, and pregnancy related factors were examined using a multivariable logistic regression. Adjusted odds ratios (OR) and 95 % confidence intervals (CI) were reported for all variables. RESULTS: The sample size was 290, weighted to represent 2224 adolescent women. Based on the adjusted model, the odds of experiencing an intended pregnancy were increased if the adolescent woman was between 18–19 years old (OR 2.62, 95 % CI 1.05, 6.57), had a partner (OR 2.37, 95 % CI 1.12, 4.99), experienced no violence/abuse (OR 3.08, 95 % CI 1.38, 6.86), and consumed no alcohol before pregnancy (OR 3.17, 95 % CI 1.56, 6.45). Additionally, adolescent women who reported drug use prior to pregnancy were more likely to have an intended pregnancy (OR 0.39, 95 % CI 0.16, 0.95). CONCLUSION: The findings from this study can be used as the basis for future research to investigate the characteristics and needs represented by this group of adolescents and to aid in the development of effective policies and programs.